Distribution of pyrethroid insecticides in secondary wastewater effluent. (18th October 2013) - Parry, Emily; Young, Thomas M.
Abstract Although the freely dissolved form of hydrophobic organic chemicals may best predict aquatic toxicity, differentiating between dissolved and particle‐bound forms is challenging at environmentally relevant concentrations for compounds with low toxicity thresholds such as pyrethroid insecticides. The authors investigated the distribution of pyrethroids among 3 forms: freely dissolved, complexed with dissolved organic carbon, and sorbed to suspended particulate matter, during a yearlong study at a secondary wastewater treatment plant. Effluent was fractionated by laboratory centrifugation to determine whether sorption was driven by particle size. Linear distribution coefficients were estimated for pyrethroid sorption to suspended particulate matter (Kid) and dissolved organic carbon (Kidoc) at environmentally relevant pyrethroid concentrations. Resulting Kid values were higher than those reported for other environmental solids, and variation between sampling events correlated well with available particle surface area. Fractionation results suggest that no more than 40% of the pyrethroid remaining in secondary effluent could be removed by extending settling periods. Less than 6% of the total pyrethroid load in wastewater effluent was present in the dissolved form across all sampling events and chemicals. Environ Toxicol Chem 2013;32:2686–2694. © 2013 SETAC